“Optimización del sistema de gestión de inventarios de la empresa Servitruck J&S” - Catagña Suntaxi, Cristhian Alexander (2023)
The present work is developed with the objective of optimizing the inventory system through a control model to ensure the stock of the company SERVITRUCK J&S, in which the causes and consequences of the main problems that are immersed in the inventory system were analyzed. inventories, the inconsistencies in the inventory registration impair the placing of orders on time, together with an inadequate space to comply with the logistics cycle, for this reason it began with the diagnosis of the procedures that the company carries out, where a unstructured interview disclosing company information describing processes and analyzing possible solutions to problems.